Comparative Analysis of Five Forensic PCR Kits in Duplets - Tamás Cseppentő; Norbert G. Valis; Gusztáv Bárány; Bálint Megadja; Attila Heinrich; Nóra M. Magonyi (DNA)
In forensic DNA laboratories, it is important to conduct internal validations of the commercially available kits of short tandem repeat (STR) loci and to investigate their individual and combined effectiveness. This study aims to report on a comparative investigation of the forensic kits used in our laboratory and their combinations in analysing low-copy-number (LCN) human DNA samples. We used five partly overlapping multiplex kits with different marker configurations from different manufacturers: the NGM SelectTM PCR Amplification Kit, NGM DetectTM, the GlobalFilerTM Amplification Kit (Applied BiosystemTM, Foster City, CA, USA), the PowerPlex® Fusion 6C System (Promega Co., Madison, WI, USA) and the Investigator® 24plex QS Kit (Qiagen GmbH, Hilden, Germany). The efficacy of the kits was scrutinised by specific criteria, such as allelic dropout rate, the individually calculated Likelihood Ratio (LR) of consensus profiles and the LR value of the composite profile produced by the combined profiles of two kits. According to the results, the pairing of PowerPlex® Fusion 6C System and Investigator® 24plex QS produced the lowest, while the pairing of the NGM DetectTM and GlobalFilerTM kits provided the highest LR value. In summary, our study is meant to aid the selection of the optimal kit combination for samples of different qualities.